Drop-Weight Impact Resistance of 3D-Printed Complex Zeolite-Inspired Structures - Ambekar, Rushikesh S.; Oliveira, Eliezer F. [UNESP]; Pugazhenthi, Piraisoodan; Singh, Shatrughan; Mahapatra, Debiprosad Roy; Galvao, Douglas S.; Tiwary, Chandra S. (Wiley, 2024)
Ballistic resistance architectures have crucial importance in the defense and aerospace industries. The researchers are constantly excited to explore lightweight, complex architectures for higher mechanical energy absorption. The complexity of the design is restricted due to a lack of advanced manufacturing techniques. However, additive manufacturing (AM)/3D printing facilitates sustainability, excellent design flexibility, and automation. The zeolite-inspired 3D printed structures are designed and developed to study deformation under low-velocity drop impact. The present work has the comparison of the specific energy absorption of different types of zeolite-inspired structures. It also has the effect of velocity on impact depth at multiscale using molecular dynamics (theoretical) and computer tomography (experimental).
Keywords: 3D printing; fracture analyses; specific impact energies; zeolite-inspired structures